Study of Carrying Capacity and Development Strategy of Coral Garden Based Ecoedutourism in Cemara Besar Island, Karimunjawa National Park, Jepara, Central Java - Yeremia Edgar Aprilio; Muhammad Arif Asadi; Yulius Yulius (Jurnal Segara, 2022)
Cemara Besar Island, Karimunjawa National Park, is an important tourist destination in the province of Central Java due to its beautiful beaches and coral reefs. The purpose of this study was to see the area carrying capacity for ecoedutourism based on coral gardens in Cemara Besar Island, analyze development strategies, and find out the recommended spots. The carrying capacity of the area is calculated using three considerations: Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC) and Effective Carrying Capacity (ECC). The results, in PCC>RCC>ECC format, are 2472>97>42 people per day in the utilization zone while 670 > 30 > 15 people per day in the protection zone. Using SWOT analysis, the analysis of tourism development strategies produced 15 alternative regional development strategies, with the top strategic priority being “the development of the concept of coral garden tourism”. Observations on five recommended spots were carried out using a time swimming method, by snorkeling for 10 minutes in an area of 10 m × 10 m per point. The two recommended points in the northern east side of the island, points B and D, are designated as the highly recommended points to apply the concept of ecoedutourism based on coral garden because in these two points the condition of coral reefs is not too good and requires restoration.